Voices from the world of Jane Austen - Day, Malcolm (Cincinnati, Ohio : David and Charles, 2007)
Draws on letters, diaries, essays, travelogues, sermons, notices, and the novels of Jane Austen to explore the people, issues, political atmosphere, and culture of Europe during Austen's life.
Includes bibliographical references and index.
Adult
Keywords: Austen, Jane, -- 1775-1817 -- Criticism and interpretation; Austen, Jane, -- 1775-1817 -- Criticism; Manners and customs in literature; England in literature; Manners and customs in literature; England -- In literature; England -- Social life and customs -- 18th century; England -- Social life and customs -- 19th century; England -- Social life and customs